Omni-Channel Customer Experience and Advancing Customer Loyalty - Md. Abdul Alim; Md. Shafiullah; Yheetishamul Khan Sazid; Kanon Datta; Md. Fida – Ul Huq; Asif Al Akib; Md. Julhaz Hossain (Asian Academy of Management Journal, 2025)
Grounded on the customer experience theory and perceived value theory, the current study examines how omni-channel customer experience (OCCE) in fashion brands promotes customer loyalty in an emerging economy context. Fashion brand customers (N = 372) revealed that OCCE significantly influences customer satisfaction, increases perceived value, and advances customer loyalty. Likewise, omni-channel customer satisfaction (SAT) and perceived value also lead to customer loyalty. The study further demonstrates that SAT and perceived value also have an indirect effect on the relationship between OCCE and customer loyalty. These important insights would contribute to advancing the existing understanding in similar domains. The theoretical and practical implications, study shortcomings, and avenues for future studies are also outlined.